Estimation of Speed and Rotor Position without Speed Sensor of Electrically Excited Synchronous Motor - WANG Shiping; HE Bojun; XIN Lanyuan; DOU Zechun; QIN Canhua (机车电传动)
A vector control method of estimating the rotor speed based on model reference adaptive system (MRAS) was put forward. The flux observation equation based on voltage model and current model was provided particularly, and the estimated speed was obtained by regulating error signal between flux estimated by current model and voltage model with PI regulated. The vector control system for electrically excited synchronous motor without speed sensor was simulated by Matlab/Simulink, and was validated that had a good speed estimation effect.